2018
DOI: 10.3390/fib6010002
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Hybrid PVA Fiber and AR-Glass Textile Reinforced Geopolymer Composites

Abstract: Textile reinforced mortar or concrete, a thin cementitious composite reinforced by non-corrosive polymer textile fabric, was developed and has been researched for its role on repair and strengthening of reinforced concrete (RC) structures. Due to embedment of polymeric textile fabric inside the cementitious matrix, many researchers argued the superiority of this technology than the externally bonded fiber reinforced polymer (FRP) sheet in RC in terms of prevention of debonding of FRP and durability in fire. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In itself, this method is already quite effective, a proven option for changing the characteristics and structure of geopolymer concrete, giving it a different nature of destruction, more viscous, as well as the entire mechanics of the structure made from such concrete. This is in good agreement with the works of other authors who used various types of fiber in geopolymer concrete technology [36][37][38][39][40][41].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In itself, this method is already quite effective, a proven option for changing the characteristics and structure of geopolymer concrete, giving it a different nature of destruction, more viscous, as well as the entire mechanics of the structure made from such concrete. This is in good agreement with the works of other authors who used various types of fiber in geopolymer concrete technology [36][37][38][39][40][41].…”
Section: Resultssupporting
confidence: 92%
“…For example, in a study [36], the introduction of 0.3% steel fiber into the composition of geopolymer concrete made it possible to achieve the best compressive strength values. In studies [37][38][39][40][41], reinforcing geopolymer composites with glass, polypropylene, basalt, and steel fibers in optimal amounts improved their physical and mechanical properties. However, the issues of geopolymer concrete, not to mention geopolymer FRC, are poorly covered in regulatory and technical documents and currently do not allow mass production flow construction.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the influence of short fibers on the mechanical properties of TRC has been investigated by numerous research groups [18][19][20][21]. The results of their studies indicate that the presence of short fibers within the cementitious matrix can improve the bonding between the textile and matrix, and thereby the flexural, tensile, and cracking strength of TRC can be improved [3,18].…”
Section: Introductionmentioning
confidence: 99%
“…To address this limitation, researchers have studied the use of various types of short, randomly distributed fibers to reinforce geopolymers and improve their tensile and flexural behavior. A number of studies have reported the use of cotton and flax fibers [2,3,4], PVA fiber [5,6], polyethylene fiber (PE) [7,8], glass fiber [9,10], carbon fiber [11], and steel fiber [5,12] to reinforce geopolymers. In all the above studies, an improvement in the flexural and tensile strength of geopolymer composites was reported due to the addition of fibers.…”
Section: Introductionmentioning
confidence: 99%